Polysaccharide-based delivery systems for curcumin and turmeric powder encapsulation using a spray-drying process - Goelo, V (2020)
Curcumin is a hydrophobic polyphenol with a large spectrum of pharmacological functions, such as anti-inflammatory, anticarcinogenic and antioxidant, among others. Due to its chemical instability, the incorporation of curcumin into carrier-based delivery systems has been proposed to improve its stabilization and bioavailability in the human body. The present work suggests the spray-drying technique for the encapsulation of curcumin and turmeric powder (with the active compound curcumin) using the polysaccharides pectin, maltodextrin, inulin and xanthan as encapsulating agents. A product yield between 7.52 and 60.60% was registered for all the micro-particles produced: empty, loaded with turmeric powder and loaded with curcumin. Microparticles with a spherical form, rough surface (pectin, maltodextrin and xanthan microparticles) and smooth surface (inulin microparticles) were produced. The fastest core compound release from curcumin- and turmeric powder-loaded microparticles was registered with inulin and maltodextrin, respectively. The most appropriate kinetic model to describe the registered release profiles is the Weibull model.